2019
DOI: 10.1371/journal.pone.0220446
|View full text |Cite
|
Sign up to set email alerts
|

The reach of commercially motivated junk news on Facebook

Abstract: Commercially motivated junk news–i.e. money-driven, highly shareable clickbait with low journalistic production standards–constitutes a vast and largely unexplored news media ecosystem. Using publicly available Facebook data, we compared the reach of junk news on Facebook pages in the Netherlands to the reach of Dutch mainstream news on Facebook. During the period 2013–2017 the total number of user interactions with junk news significantly exceeded that with mainstream news. Over 5 Million of the 10 Million Du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Useful videos did not exceed misleading ones in popularity, which suggests that the chance of a layperson being exposed to inaccurate information is quite high. Unfortunately, fake news spreads six times faster than verified news and receives higher viewer interaction [ 58 , 59 ]. Biggs et al [ 37 ] reported that misleading videos are more viewed than useful videos because the useful ones have longer running times; however, recent studies on COVID-19–related YouTube videos have returned inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Useful videos did not exceed misleading ones in popularity, which suggests that the chance of a layperson being exposed to inaccurate information is quite high. Unfortunately, fake news spreads six times faster than verified news and receives higher viewer interaction [ 58 , 59 ]. Biggs et al [ 37 ] reported that misleading videos are more viewed than useful videos because the useful ones have longer running times; however, recent studies on COVID-19–related YouTube videos have returned inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…While Dutch news consumers have been found to use a variety of news sources, the Netherlands also has a steady 'pulp news' diet (Burger et al, 2019;van der Poel, 2019). From 2013-2017 Dutch Facebook users consumed more low-quality, commercially driven clickbait than mainstream news, as was found through engagement scores.…”
Section: Dutch Fake Followers and Trollsmentioning
confidence: 99%
“…Facebook created by two college students which are named Mark Zuckerberg along with Edward Saverin, and it's began in February of 2004. Nowadays, after 17 years of existing, Facebook has become the largest user friendly social network website and global phenomenon [1], [2]. Currently, there are over 2.8 billion monthly users worldwide are active participants in the communities (Facebook, 2021) as of March, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on this topic [12], [17], [28], [40], [41], [41], [42]. It is reported that Facebook addiction has become a universal concern and considered as a health issue [43], although it has been a worldwide problem among university students and youth generation [2], [10], [17], [28], [40], [42], [44]. It is clear that the symptoms of Facebook addiction can be exhibited in attitudes [45], cognition [46], physical and emotional reaction [47], and interpersonal and psychological problems [7], [34], [44], [48].…”
Section: Introductionmentioning
confidence: 99%